2019
DOI: 10.1002/pra2.35
|View full text |Cite
|
Sign up to set email alerts
|

Systematic examination of pre‐ and post‐retraction citations

Abstract: Scientific retractions occur for a multitude of reasons. A growing body of research has studied the phenomenon of retraction through systematic analyses of the characteristics of retracted articles and their associated citations. In our study, we focus on the characteristics of articles that cite retracted articles, and the changes in citation dynamics pre‐ and post‐retraction. We leverage descriptive statistics and ego‐network methods to examine 4,871 retracted articles and their citations before and after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Bar-Ilan and Halevi (2018) reported that post-retraction 608 citations increased; however, the growth rates of post-retraction citations dropped across their three data collection dates. Dinh et al (2019) and Mott et al (2019) reported that retracted papers' citation counts dropped after the retraction. Our longitudinal analysis on the shares of active retracted papers in each retraction year across the citation years answers RQ1 and provides further insight into the post-retraction decrease in citation counts: old retracted papers have stopped being 613 cited as time progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bar-Ilan and Halevi (2018) reported that post-retraction 608 citations increased; however, the growth rates of post-retraction citations dropped across their three data collection dates. Dinh et al (2019) and Mott et al (2019) reported that retracted papers' citation counts dropped after the retraction. Our longitudinal analysis on the shares of active retracted papers in each retraction year across the citation years answers RQ1 and provides further insight into the post-retraction decrease in citation counts: old retracted papers have stopped being 613 cited as time progressed.…”
Section: Discussionmentioning
confidence: 99%
“…Their 92 results showed that post-retraction citation counts were significantly lower than pre-retraction citation counts (Dinh et al, 2019). Moreover, for 250 retracted articles with the same pre-retraction and post-retraction timeframe, citation counts decreased in the post-retraction timeframe for 96% (240/250) of the retracted articles (Dinh et al, 2019). Chen et al (2013) and Shuai et al (2017) studied retracted papers indexed in Web of Science (WoS).…”
mentioning
confidence: 99%
“…While some studies primarily analyze citation contexts (e.g., Suelzer et al 2019) or citation statistics (e.g., Peterson 2013), we are aware of three studies that have drawn on synergies between citation context analysis and network visualization perspectives (Chen et al 2013;Dinh et al 2019; van der Vet and Nijveen 2016). The most similar to the present work (van der Vet and Nijveen 2016) presents a case study of citation networks and citation contexts for a single retracted paper that was published in Nature in December 2012 and retracted in February 2014.…”
Section: Combining Citation Context Analysis and Network Analysismentioning
confidence: 99%
“…The Retraction Watch Database 1 lists over 23,000 retracted publications as of May 2020. In biomedicine 94% of retracted papers have received at least one citation, with an average citation count of 35 [15]. Nor are all citations to these articles negative; even Wakefield's fraudulent paper linking the MMR vaccine to autism received 94 positive citations [42].…”
Section: Scope and Importance Of The Problemmentioning
confidence: 99%
“…2006's Refs [15][16][17][18][19] that had reported the reduction of PSD-95 early in neurodegeneration (including in Alzheimer's disease). However, unlike the pass-through keystone citations seen in the first case study, which are tangentially supported by main findings (though not of the cited paper itself), in this case, this support comes from an informal literature review, Zhao's introduction, which is cited for the statement "PSD-95 decreases early in neurodegeneration.…”
Section: Keystone Citations Support Experimental Materialsmentioning
confidence: 99%